2018
DOI: 10.1002/wcms.1388
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on computational simulations of glycosaminoglycans

Abstract: Glycosaminoglycans (GAGs) represent a formidable frontier for chemists, biochemists, biologists, medicinal chemists, and drug delivery specialists because of massive structural complexity. GAGs are arguably the most complex, natural linear biopolymers with theoretical diversity orders of magnitude higher than proteins and nucleic acids. Yet, this diversity remains generally untapped. Computational approaches offer major routes to understand GAG structure and dynamics so as to enable novel applications of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 243 publications
(606 reference statements)
0
31
0
Order By: Relevance
“…One of these is CD44, and it has been observed using murine models that the recruitment of macrophages and neutrophils into sites of inflammation is CD44-dependent [ 37 , 38 , 39 ]. Hyaluronan is a linear glycosaminoglycan that is formed by alternating disaccharide units of repeating (1→3)-β- d -GlcNAc and (1→4)-β- d -GlcA residues [ 40 , 41 ]. Some studies have shown that hyaluronan of different molecular weights can be covalently attached to the surface of nanoparticles to engage the activity of targeted hyaluronan receptors (CD44 and CD168), which are used in various carcinoma cells (e.g., ovarian, colon, and stomach) or innate immune cells (e.g., macrophages) [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of these is CD44, and it has been observed using murine models that the recruitment of macrophages and neutrophils into sites of inflammation is CD44-dependent [ 37 , 38 , 39 ]. Hyaluronan is a linear glycosaminoglycan that is formed by alternating disaccharide units of repeating (1→3)-β- d -GlcNAc and (1→4)-β- d -GlcA residues [ 40 , 41 ]. Some studies have shown that hyaluronan of different molecular weights can be covalently attached to the surface of nanoparticles to engage the activity of targeted hyaluronan receptors (CD44 and CD168), which are used in various carcinoma cells (e.g., ovarian, colon, and stomach) or innate immune cells (e.g., macrophages) [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing amount of work is mainly devoted to the comprehension of the dynamic behavior of GAGs (which are characterized by an ensemble of conformations rather than a single secondary or tertiary structure). Additionally, there is an increased focus on the characterization of the conformational changes occurring in GAGs and proteins following their mutual interaction [ 9 ].…”
Section: Fundamentals Of Molecular Modeling Docking and MD Simulations In Glycobiologymentioning
confidence: 99%
“…Among the computational methods that can boost the understanding of how GAGs/PGs bind to proteins, particularly promising are molecular modeling, docking and molecular dynamics (MD) simulations. In effect, by working in a virtual environment, these methodologies benefit from a high resilience and potential for high throughput [ 7 , 8 , 9 , 10 ]. Briefly, molecular modeling uses molecular mechanics models to construct three-dimensional molecular structures; molecular docking gives favorable arrangements of molecules in complexes (e.g., GAG/protein complexes); MD simulations reproduce the dynamic behavior of individual molecules or complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in principle, their interactions can be characterized in silico. In recent years, much effort has gone into this arena, including developing energy functions, MD and docking programs, and user-friendly software that can be accessed by the GAG community at large (107)(108)(109)(110)(111)(112). Promising variants from this exercise could then be tested by experimental methods.…”
Section: Future Directions and Challengesmentioning
confidence: 99%